1958
DOI: 10.2134/agronj1958.00021962005000090010x
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Diallel Crosses Among Ten Varieties of Soybeans1

Abstract: Synopsis Three methods of statistical analysis were similar in detecting lines exhibiting unexpected performance in the F1 generation, but gave different estimates on which were based the interpretations of parental‐F1 relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
8

Year Published

1959
1959
2001
2001

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 7 publications
2
20
0
8
Order By: Relevance
“…New findings on cytoplasmic male sterility (Davis 1986) and somatic embryogenesis (Komatsuda and Ohyama 1988) (Jinling and Fanglan 1985 (Brim and Cockerham 1961;Weber et al 1910' Nelson andBernard 1984). Significant positive heterosis for oil has been found (Leffel and Weiss 1958;Sabbouh 1987 Soldati and Keller (1985) in Switzerland …”
Section: Stittistical Proceduresmentioning
confidence: 97%
“…New findings on cytoplasmic male sterility (Davis 1986) and somatic embryogenesis (Komatsuda and Ohyama 1988) (Jinling and Fanglan 1985 (Brim and Cockerham 1961;Weber et al 1910' Nelson andBernard 1984). Significant positive heterosis for oil has been found (Leffel and Weiss 1958;Sabbouh 1987 Soldati and Keller (1985) in Switzerland …”
Section: Stittistical Proceduresmentioning
confidence: 97%
“…A variância de dominância também apresenta importância para alguns caracteres: produtividade de grãos e altura da planta (Leffel & Weiss, 1958), periodo reprodutivo e produtividade de grãos (Brim & Cockerham, 1961); altura da planta (Croissant & Torrie, 1971). Em alguns casos, pode ocorrer da variância dominante ser superior à variância aditiva, como foi observado por Chaudary & Singh (1974) para produtividade de grãos; por Leffel & Hanson (1961) para produtividade, maturidade e altura da planta; por Camacho (1971) para periodo reprodutivo e altura da planta no florescimento.…”
Section: Produtividade Altura Da Planta E Valor Agronômicounclassified
“…Most evidence suggests that maturity is primarily a func tion of additive gene action (Weber, 1950;Mahmud andKramer, 1951» Homer andWeber, 1956;Leffel and Weiss, 1958;Gates et al, I96O;Hanson and Weber, 1962;Weber et al, 1970;Bernard, 1971;Croissant and Torrie, 1971;Thseng and Hosokawa, 1972b;and Lee et al, 1974), but Hanson et al (I967) reported that half of the total genotypic variance was due to epistasis.…”
Section: Maturitymentioning
confidence: 99%
“…Several reports (Kalton, 1948;Leffel and Weiss, 1958;Nagata, 1960a;Brim and Cockerham, 196I;Tang and Tai, 1962;Caviness and Prongsirivathana, I968;and Weber et al, 1970) indicated that dominance was the most important type of gene action, with tall dominant to short. Mahmud and Kramer (1951), Thseng et al (I971), and Croissant and Torrie (1971) showed that additive gene action comprised most of the genotypic variance for plant height.…”
Section: Plant Height At Maturitymentioning
confidence: 99%